Using Holograms in Teaching (Comprehensive Journal of Science, 2025)
Holograms for teaching are an advanced teaching tool that enhances the efficiency of student participation in the process of learning. The three-dimensional visualizations in holograms will give students a better opportunity to achieve knowledge interactively and entertainingly, which could explain some very complex concepts better and help provide better understanding. This would help students visualize what they cannot view directly with ordinary means: anatomy, historical items, scientific models, etc. Besides, holograms can enable distant learning through the realistic and life-like representation of subjects, beating the barriers of geographical distance. Though there are challenges, including cost and technical limitations, the potential of holographic learning tools in classrooms is huge; these make education more dynamic and engaging.
Keywords: Holography Education 3D Visualization E-learning Teaching Technology